BALANCED PRICING MODEL BASED ON THE ANALYSIS OF THE ORDER PROFITABILITY - Kozhushkin, M. E. (Science and Transport Progress, 2009)
The mechanism of agreement process for a contract price on pipe products is offered taking into account the dates of deliveries and specificity of forming the prime price of an order. During the formation of sale cost the level of profitability of every constituent and the whole order is taken into account.